ЗБИРКА ВЛАСТИМИРА СТАНИМИРОВИЋА НЕКИ ОБИЧАЈИ (О УБИЈАЊУ СТАРАЦА) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
The work represents the description of the collection Remarkable customs (regarding killing of the old men) by Vlastimir Stanimirović, which is in the Ethnographic collection of the Archive of SANU under the number 325/12. The collection can be determined as a thematic considering that all of the telling is referring by theme and motive to lapot or the custom of killing the old people. By analyzing them, the characteristics of the genre and inter-genre pervasion of these forms of telling, the composition, the motives, the characters, and also the processes which are found as characteristic for narration noted in Stanimirović’s collection are being determined.